Epidemiology of participants in a prospective cohort study on pediatric acute kidney injury in South Korea - Naye Choi; Hee Gyung Kang; Nanhee Park; Jayoun Kim; Yo Han Ahn (Childhood Kidney Diseases)
Purpose Acute kidney injury (AKI) is a common and life-threatening complication in hospitalized patients, leading to increased hospital stays and higher mortality rates. In South Korea, prospective studies that comprehensively describe the epidemiology of AKI in this population are lacking. This study aimed to evaluate the demographic characteristics of AKI in children treated at a tertiary care center in South Korea. Methods This prospective cohort study included children who were diagnosed with AKI at a single tertiary center between February 2016 and July 2021. Results Of the 781 enrolled patients, 763 were analyzed. The cohort had a mean age of 6.72 years, and 442 patients (57.9%) were male. Hemato-oncologic diseases (202 patients, 26.5%) were the most common underlying condition, followed by preterm infants (128 patients, 16.8%) and kidney disease (108 patients, 14.2%). Nephrotoxic agent exposure (165 patients, 21.6%) represented the leading cause of AKI, followed by infection (135 patients, 17.7%), severe illness (127 patients, 16.6%), and dehydration (121 patients, 15.9%). Patients frequently presented with AKI stage 1 (363 patients, 47.6%). In patients without underlying conditions (96 patients), stage 3 AKI occurred most frequently (40 patients, 41.7%) with a greater tendency for AKI progression (25 patients, 26.0%). However, this group also experienced a higher recovery rate (81 patients, 84.4%). Conclusions This study offers a comprehensive understanding of pediatric AKI in Korea. These findings highlight the complexity of pediatric AKI and underscore the significance of tailored management strategies based on patient characteristics and AKI etiologies.